2013
DOI: 10.1007/s10461-013-0591-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Non-adherence to Clinical Follow-up Among Patients Participating in a Randomized Trial of Pharmaceutical Care Intervention in HIV-Positive Adults in Southern Brazil

Abstract: Pharmaceutical care (PC) has been shown to improve adherence to therapeutic interventions as well as improve clinical outcomes. We assessed the predictors of non-adherence to clinical follow-up (i.e., not attending three scheduled routine clinical visits over a 1 year period) among patients who participated in a clinical trial of PC intervention on adherence to HIV antiretroviral therapy uptake (the PC-HIV trial). A total of 332 patients participated: median age was 39 years, 63 % were male, 76 % had CD4 count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
1
5
0
5
Order By: Relevance
“…4 The ART adherence rates in Brazil vary from 20% to 84%. [5][6][7][8][9] However, the way in which this adherence to therapy is measured differs between studies. In a meta-analysis on ART adherence rates in Latin American and Caribbean countries, Costa et al 10 found that they varied according to the length of time over which the measurement was made.…”
Section: Introductionmentioning
confidence: 99%
“…4 The ART adherence rates in Brazil vary from 20% to 84%. [5][6][7][8][9] However, the way in which this adherence to therapy is measured differs between studies. In a meta-analysis on ART adherence rates in Latin American and Caribbean countries, Costa et al 10 found that they varied according to the length of time over which the measurement was made.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Further, these studies tend to have a more robust and formalised data collection system, with increased financial incentive to maintain low levels of missing data or use enhanced strategies to prevent loss in follow-up. 40 Our findings should be interpreted with caution as our study sample only included articles with full-text availability. Furthermore, studies that were not published in English, conference studies and grey literature were not included, which may limit the generalisability of our findings.…”
Section: Discussionmentioning
confidence: 86%
“…We conducted a historical cohort study nested in the PC‐HIV randomized clinical trial (NCT00959361) to assess the effectiveness of pharmaceutical care on the adherence to antiretroviral therapy. Details and results from the trial are published elsewhere . In brief, 332 individuals 18 years old or more, under treatment with HAART, who seek medical assistance at HIV/AIDS Assistance Service‐SAE/UFPEL, Pelotas, Brazil, between June 2006 and July 2007, were randomized to usual care assistance only or additional pharmaceutical care.…”
Section: Methodsmentioning
confidence: 99%
“…Socio‐demographic characteristics were assessed by a structured interview, including information on sex, age, family income, education and if living alone or with others. Treatment adherence was evaluated through self‐report questionnaire on pills intake in the past 3 days . The self‐report questionnaire consisted in a time sheet used to help the patient remember his/her routine activities (e.g.…”
Section: Methodsmentioning
confidence: 99%